Role and Responsibilities of The Government in Protecting Indonesian Migrant Workers Abroad Based on Legal Protection from a Human Rights Perspective - Anggriani, Reni; Chairi, Ahmad Ramdani; Liani, Sesi Safitri (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
The Indonesian government through Law Number 18 of 2017 has the main responsibility for providing legal protection for migrant workers, which includes the phases before, during and after work abroad. It is important for the government and law enforcement to provide education and provide information to prospective migrant workers, as well as support and assistance provided by consular services in the destination country. Despite significant efforts, challenges in implementing protection policies still need to be overcome to improve the welfare of migrant workers. The method used in this research is a normative juridical research method. Focusing and analyzing legal documents allows writers to identify and interpret relevant legal norms to analyze the impact and application of relevant laws.